1995
DOI: 10.1176/ajp.152.8.1130
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-induced mania and cycle acceleration: a controversy revisited

Abstract: Mania is likely to be antidepressant-induced and not attributable to the expected course of illness in one-third of treatment-refractory bipolar patients, and rapid cycling is induced in one-fourth. Antidepressant-induced mania may be a marker for increased vulnerability to antidepressant-induced cycle acceleration. Antidepressant-induced cycle acceleration (but not antidepressant-induced mania) is associated with younger age at first treatment and may be more likely to occur in women and in bipolar II patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(38 citation statements)
references
References 72 publications
1
37
0
Order By: Relevance
“…Whereas some studies have reported benefit from continuation antidepressant therapy in patients who have recovered from bipolar depression (Altshuler et al, 2009; Amsterdam et al, 1998; Amsterdam and Shults, 2010a, b; Kupfer et al, 2001), other studies have not confirmed this finding or have reported increased mood conversion rates during continuation antidepressant use (Altshuler et al, 1995; Ghaemi et al, 2004; Leverich et al, 2006; Sachs et al, 2007; Vieta, 2008; Viktorin et al, 2014). A retrospective chart review study by Altshuler et al (2001) examined the risk of depressive relapse over one year in recovered bipolar depressed subjects who either continued or discontinued antidepressant therapy.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Whereas some studies have reported benefit from continuation antidepressant therapy in patients who have recovered from bipolar depression (Altshuler et al, 2009; Amsterdam et al, 1998; Amsterdam and Shults, 2010a, b; Kupfer et al, 2001), other studies have not confirmed this finding or have reported increased mood conversion rates during continuation antidepressant use (Altshuler et al, 1995; Ghaemi et al, 2004; Leverich et al, 2006; Sachs et al, 2007; Vieta, 2008; Viktorin et al, 2014). A retrospective chart review study by Altshuler et al (2001) examined the risk of depressive relapse over one year in recovered bipolar depressed subjects who either continued or discontinued antidepressant therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Long-term antidepressant therapy for relapse-prevention of bipolar depression has received relatively little attention (Altshuler et al, 2003; Altshuler et al, 1995; Bond et al, 2008; Ghaemi et al, 2001; Ghaemi et al, 2004). Whereas some studies have reported benefit from continuation antidepressant therapy in patients who have recovered from bipolar depression (Altshuler et al, 2009; Amsterdam et al, 1998; Amsterdam and Shults, 2010a, b; Kupfer et al, 2001), other studies have not confirmed this finding or have reported increased mood conversion rates during continuation antidepressant use (Altshuler et al, 1995; Ghaemi et al, 2004; Leverich et al, 2006; Sachs et al, 2007; Vieta, 2008; Viktorin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anger attacks showed good response to antidepressants alone in MDD [11], and the rate of switch into mania or hypomania with monotherapy with antidepressants was comparable in MDD with and without anger attacks [14]. On the other hand, antidepressants alone can increase anger and mood instability in bipolar depression [2, 4, 6, 7, 8, 15, 16, 17, 18, 19, 20, 21, 22]. Given the apparent different impact of antidepressants on anger in MDD and in bipolar disorders, it is important for clinicians to know if MDD with anger is closer to bipolar disorders than to MDD.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that ADs may increase the risk of manic induction and cycle acceleration 911. Furthermore, both anxiety disorder comorbidity, which has a lifetime prevalence of 45% in individuals with BPs,12 and exposure to a greater number of AD trials have been suggested as independent predictors of prospective long-term nonresponse to treatment 13.…”
Section: Introductionmentioning
confidence: 99%